(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To evaluate differences in craniofacial skeletal pattern among subjects with competent and incompetent lip seal (ILS). Methodology: Sample of 261 subjects (177 females and 84 males) was constituted by random selection from patients who visited Orthodontic OPD. Lip seal was assessed by clinical examination on the basis of visual inspection of muscular tension in the mental region at mandibular rest position and subjects were divided into competent lip seal and incompetent lip seal group. Skeletal measurements were performed on lateral cephalograms to assess differences in vertical and sagittal skeletal pattern among subjects in both groups. Results: Competent lip seal was found in 64.4 % of the subjects and 35.6% of subjects had incompetent lips. ILS group had greater values of SNA and ANB whereas SNB value was reduced. The inclination of maxilla (SNPP) was larger in competent lip group and inclination of mandible (SNMP) was larger in incompetent lip group. Statistically significant differences were found between the two groups in the interbasal relationship (PPMP), Y-axis angle and anterior lower facial height ratio, with increased values of these measurements in incompetent lip group. Posterior facial height ratio was comparatively reduced in subjects with ILS. Conclusion: Patients with ILS have higher tendency to develop class II skeletal pattern with mandibular retrognathia, increased inclination of mandibular plane and tendency for clockwise rotation of mandible. Lip incompetence also leads to vertical growth pattern resulting in increased anterior lower face height and decreased posterior facial height